2013
DOI: 10.9790/0853-0843032
|View full text |Cite
|
Sign up to set email alerts
|

Light Energy Conversion Toothbrush (Soladeytm) Towards a Super Clean Mouth! : A Review

Abstract: Oral hygiene is the practice of keeping the mouth clean to prevent dental decay. Cleaning the teeth is the process of removing dental plaque, which mainly consist of streptococcus mutans bacteria. Streptococcus mutans contribute towards tooth decay. Prolonged plaque presence increases the likelihood of cavities, gum diseases and gingivitis. The need for good oral hygiene is obvious and is achieved mostly through brushing the teeth with a fluoride treated toothpaste and toothbrush. The Soladey TM toothbrush dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…They found that the brushes included an n-type TiO 2 , in which the electrons get excited upon exposure to sunlight, leading to a metal ion reduction process. 353 Hoover et al reported that solar brushes significantly reduced plaques on the mandibular edges of all dentitions efficiently than regular brushes. 354 4.1.5 Drug delivery.…”
Section: Energy and Environmental Science Reviewmentioning
confidence: 99%
“…They found that the brushes included an n-type TiO 2 , in which the electrons get excited upon exposure to sunlight, leading to a metal ion reduction process. 353 Hoover et al reported that solar brushes significantly reduced plaques on the mandibular edges of all dentitions efficiently than regular brushes. 354 4.1.5 Drug delivery.…”
Section: Energy and Environmental Science Reviewmentioning
confidence: 99%